2008
DOI: 10.1097/mca.0b013e3282f3fbde
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and carotid lesions are strong predictors of clinical events in patients with early stages of atherosclerosis: a 24-month follow-up study

Abstract: In this study, endothelial dysfunction and carotid lesions significantly increased the risk of vascular events in asymptomatic patients with early stages of atherosclerosis. Assessment of systemic vasoreactivity and carotid IMT evaluation may provide, in this category of patients, important prognostic information in addition to that derived from traditional established cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 20 publications
2
58
1
Order By: Relevance
“…We observed that lower FMD correlated with higher serum creatinine, suggesting that impaired endothelial function may be associated with renal dysfunction in hypertensive patients. Several studies have shown a significant correlation between FMD and carotid IMT, 20,21 a result that is echoed in this study. Other studies reported different results.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We observed that lower FMD correlated with higher serum creatinine, suggesting that impaired endothelial function may be associated with renal dysfunction in hypertensive patients. Several studies have shown a significant correlation between FMD and carotid IMT, 20,21 a result that is echoed in this study. Other studies reported different results.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we found that FMD in hypertensive patients was inversely related with serum creatinine, cf-PWV, carotid IMT and LVMI, as reported earlier. [20][21][22] However, we identified no relationship between FMD and UACR. We observed that lower FMD correlated with higher serum creatinine, suggesting that impaired endothelial function may be associated with renal dysfunction in hypertensive patients.…”
Section: Discussioncontrasting
confidence: 44%
“…30 The subjects with abnormalities in both these studies not only had prediabetes, but also had PreHTN. Circadian BP variability abnormalities 31,32 and endothelial dysfunction 33 are both early markers for an elevated risk of developing CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is a barometer for the early stage of atherosclerosis [13] and a predictor for cardiovascular events [14,15]. Both RA and SLE are associated with endothelial dysfunction [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%